Survivals of the Intraoperative Motor-evoked Potentials Response in Pediatric Patients Undergoing Spinal Deformity Correction Surgery: What Are the Neurologic Outcomes of Surgery?. Issue 16 (15th August 2019) - Wang, Shujie; Li, Chaoxiong; Guo, Lanjun; Hu, Haimei; Jiao, Yang; Shen, Jianxiong; Tian, Ye; Zhang, Jianguo
Abstract : Study Design: This is a retrospective cases study from a prospective patient register. Objective: To clarify the clinical implication regard to the survivals of motor-evoked potential (MEP) response. Summary of Background Data: Intraoperative neurophysiological monitoring has become an essential component for decreasing the incidence of neurological deficits during spine surgeries. Significant motor-evoked potential (MEP) loss but does not vanish completely is common especially in some high-risk and complicated pediatric spine deformity surgeries. Methods: A total of 1820 young patients (mean age = 12.2 years) underwent spinal deformity correction were mainly analyzed. Intraoperative monitoring (somatosensory-evoked potential, MEP, free-run electromyography, free-run electromyography) and postoperative neurologic outcomes were mainly analyzed in this study. All patients with monitoring alerts were divided into two groups: group 1, intraoperative MEP recovery group; and group 2, no obvious MEP recovery group. Moreover, the patients would be followed up strictly if he/she showed IOM alerting. The surviving MEP response was identified as significant monitoring alerts (80%–95% MEP Amp. loss) associated with high-risk surgical maneuvers. Results: The results showed that there were 32 pediatric patients (group 1, 21 cases and group 2, 11 cases) presenting significant MEP monitoring alerts (80%–95% loss) relative to baseline. The patients in group 1 presented the partial/entire signal recovery from MEP alerts and they did not show spinal cord deficits postoperation. The patients in group 2 without obvious intraoperative MEP recovery showed different levels of new spinal deficits, no patient showed postoperative complete paraplegia or permanent spinal cord/nerve root deficits. Conclusion: When the intraoperative MEP changes significant and persistent but without totally disappeared, the rate of postoperative neural complication is relatively low. The chance of recovery of these neurological deficits is very high. Therefore, this phenomenon may be used to predictive of nonpermanent paraplegia. Level of Evidence: 3 Abstract : The phenomenon that significant motor-evoked potential (MEP) drops but does not vanish completely is becoming common during high-risk and complicated spine surgeries for pediatric patients. The surviving MEPs may indicate transient new spinal deficits but probably not disastrous complete paraplegia.